Nociceptive Threshold of Calves and Goat Kids Undergoing Injection of Clove Oil or Isoeugenol for Disbudding - Frahm, Sandra (Animals (Basel), 2020)
SIMPLE SUMMARY: Hot-iron disbudding in calves and goat kids is a widespread husbandry procedure involving pain and, especially in goats, the risk of brain damage. The injection of clove oil under the horn bud is a potential alternative disbudding method. Clove oil, with its active substance eugenol, is cytotoxic but has anaesthetic effects, and the injection of clove oil, or the pure substance isoeugenol, under the horn bud to stop horn growth may have potential welfare benefits compared to hot-iron disbudding. We compared the injection of clove oil with the injection of isoeugenol under the horn bud with respect to pain sensitivity in this area in the first 24 h after injection. Compared to before injection, the pain sensitivity of goats kids was higher 24 h after injection of clove oil and up to at least 6 h after isoeugenol injection, while, in calves, pain sensitivity was highest after 9 h. Future studies should compare the welfare effects of isoeugenol injection with hot-iron disbudding. ABSTRACT: In this preliminary study, we compared changes in mechanical nociceptive thresholds (MNT) of calves and goat kids injected with clove oil or isoeugenol under the horn bud as a potential, more welfare-friendly alternative to hot-iron disbudding. Twenty male calves and goat kids were randomly allocated to clove oil (n = 10 per species) or isoeugenol (n = 10 per species) injection under the horn buds. MNT was measured via a pressure algometer in calves and kids at several locations around the horn buds at several time points before and up to 24 h after injection. In kids, von Frey filaments were used additionally at the same time points. In calves, linear mixed models revealed an effect on MNT of time point (p = 0.010) and side (p = 0.007), but not of injection (p = 0.298), nor of the interaction ‘injection*time point’, MNT waslowest 9 h post-injection. In goats, there was an effect of injection depending on time point (interaction injection*time point, p = 0.03) with MNT being lowest 24 h post-injection for clove oil, while MNT was similar to pre-injection in isoeugenol. In both species, variation in the individual response post-injection was very high. Our results suggest that clove oil and isoeugenol induced hypersensitivity, which was higher for clove oil, in goat kids, but they also suggest a transient anaesthetic effect in some animals and locations.